Polyethylene Glycol as an Ice Control Coating - Itagaki,K (1984)
The properties of polyethylene glycol (PEG) as a sacrificial ice control coating are discussed. PEG is effective longer than many single component coatings, and it has low toxicity and a high flash point. The results of preliminary experiments on PEG's ability to control snow accumulation on a panel and ice accumulation on a cryogenic tank are also discussed. Originator furnished keywords include: Cold regions, Ice control, Ice prevention, Polyethylene glycol, Space shuttles.